Pengaruh Pengurangan Hukuman Pada Pembiasaan Shalat Shubuh Berjamaah Terhadap Karakter Disiplin Peserta Didik - Khofifatunnisa Khofifatunnisa; Achmad Juhaeni; Ahmad Munji; Bahyati Bahyati; Faizudin Faizudin (LPPM UM Metro, 2026)
This study investigates the impact of reducing punishment for missing congregational Subuh (Fajr) prayers on students' disciplinary character at the Al-Hasyimiyah Cilegon Modern Islamic Boarding School. While positive habituation through structured routines builds discipline, altering the enforcement system poses challenges for educational institutions seeking effective coaching methods. Using a quantitative correlational approach, researchers sampled 74 students from the boarding school population. The simple linear regression analysis revealed a significant F-value of 36,858 with a significance value 0.,000 < 0.05, demonstrating that the reduction in punishment significantly affects students' disciplinary development. Furthermore, the Coefficient of Determination 0,339 indicates that this specific enforcement adjustment explains 33,9% of the variance in student discipline, while the remaining 66.1% is influenced by external factors outside the scope of this study.